Improving the thermal processing of foods (CRC Press, 2004)
The book summarises key research both on improving particular thermal processing techniques and measuring their effectiveness. Part 1 examines how best to optimise thermal processes, with chapters addressing safety and quality, efficiency and productivity and the application of computational fluid dynamics. Part 2 focuses on developments in technologies for sterilisation and pasteurisation with chapters on modelling retort temperature control and developments in packaging, sous-vide and cook-chill processing. There are chapters covering continuous heat processing, including developments in tubular heat exchangers, aseptic processing and ohmic and air impingement heating. The fourth part considers the validation of thermal processes, modelling heat penetration curves, using data loggers and time-temperature integrators and other new measuring techniques. The final group of chapters detail methods of analysing microbial inactivation in thermal processing and identifying and dealing with heat-resistant bacteria